Viewing injury in dancers from a psychological perspective: A literature review - Pollitt, E. E.; Hutt, K. (Journal of Dance Medicine & Science, 2021)
It has been reported that injury among dancers has a lifetime incidence of 90%, and recent research suggests that up to 60% of those dancers injured will meet the requirements for clinical referral to a psychologist. This study aims to review the existing literature in the field of dance psychology that focuses on psychological antecedents and responses to injury. Several relevant theories in dance psychology are reviewed. From this literature, it is suggested that psychological techniques can be taught in educational settings to equip dance students with the necessary tools to look after their bodies and minds, reduce the risk of injury, and aid in healing existing injuries. Greater emphasis should also be placed on combining physical and psychological support to improve holistic care and treatment of dancers` injuries.